Evaluation on processing suitability of 17 juice orange varieties planted in three gorges reservoir area of China - WANG, Jun; GAN, Yi; LI, Gui-Jie; HUANG, Xue-gen; TAN, An-qun; HUANG, Lin-hua; MA, Ya-qin; CHENG, Yu-Jiao; JIA, Jian-Song; ZHANG, Teng-Hui; WU, Hou-jiu (Food Science and Technology, 2023)
From 2014 to 2021, 17 sweet orange varieties and strains were continuously tested for their suitability for orange juice processing, focusing on the physical and chemical indicators of the fruit, namely juice yield, soluble solids, titratable acid, vitamin C, and sensory indicators including color value, defects, and flavor. We developed a numerical (percentage) method to evaluate the processing suitability for the juicing varieties, and all the tested data were processed using this method. A total of 12 sweet orange varieties with early, middle, and late maturity suitable for juicing were screened out, including six early matured varieties: Early Longleaf, Yuzaocheng, Westin, Early Gold, Yunguicheng, and Hamlin; two middle matured varieties: Middle Longleaf and Edangan (Jincheng); and four late matured varieties: Spring orange, Late Longleaf, Algerian Valencia, and Olinda Valencia. At the same time, five varieties, including the Early-maturings: Itaborai and Early Marrs; and the Middle-maturings: Tongshui 72-1, Trovita, and Midsweet, which can be juiced were also screened out. Among the 17 recommended varieties, the Early, Middle, and Late Longleaf are the most prominent.